Post Modern Architecture Application on One Tree Hill Hotel Resort - Firman Eddy; Mhd.Bismar Harahap (International Journal of Architecture and Urbanism, 2019)
Resort hotels are hotels built on tourist attractions, mountains, beaches, and lakes. In this design, there is a problem, namely the Contour site, located at an altitude of 1675 masl; there is a very diverse local wisdom. The purpose of this hotel development course is as an accommodation facility from tourist activity, developing the Simalem Park area, preserving the local wisdom of North Sumatra. This resort hotel not only provides accommodation facilities, but it also has elements of local wisdom from seven tribes in North Sumatra. Of the seven tribes in North Sumatra, ethnic characteristics are designed as facades or ornaments, as a way to support sustainability and appreciate the local wisdom in North Sumatra. The theme is Respect To The Traditions which functions to revitalize local wisdom with a more visible appearance. Modern but do not forget the rules that existed in the past, as a design methodology. The results of this design were built in One Tree Hill resort hotel. This design was made as an analysis, concept, and solution for Simalem Park managers who planned to build a resort hotel in One Tree Hill.